Preparation of monoPEGylated Cyanovirin-N's derivative and its anti-influenza A virus bioactivity in vitro and in vivo. (20th February 2015) - Wu, Chongchao; Chen, Wei; Chen, Jia; Han, Bo; Peng, Zhou; Ge, Feng; Wei, Bo; Liu, Mingxian; Zhang, Meiying; Qian, Chuiwen; Hou, Zhibo; Liu, Ge; et al.
Abstract: Influenza A virus (IAV) has been raising public health and safety concerns worldwide. Cyanovirin-N (CVN) is a prominent anti-IAV candidate, but both cytotoxicity and immunogenicity have hindered the development of this protein as a viable therapy. In this article, linker-CVN (LCVN) with a flexible and hydrophilic polypeptide at the N-terminus was efficiently produced from the cytoplasm of Escherichia coli at a >15-l scale. PEGylation at the N-terminal α-amine of LCVN was also reformed as 20 kDa PEGylated linkered Cyanovirin-N (PEG20k –LCVN). The 50% effective concentrations of PEG20k –LCVN were 0.43 ± 0.11 µM for influenza A/HK/8/68 (H3N2) and 0.04 ± 0.02 µM for A/Swan/Hokkaido/51/96 (H5N3), dramatically lower than that of the positive control, Ribavirin (2.88 ± 0.66 × 10 3 µM and 1.79 ± 0.62 × 10 3 µM, respectively). A total of 12.5 µM PEG20k –LCVN effectively inactivate the propagation of H3N2 in chicken embryos. About 2.0 mg/kg/day PEG20k –LCVN increased double the survival rate (66.67%, P = 0.0378) of H3N2 infected mice, prolonged the median survival period, downregulated the mRNA level of viral nuclear protein and decreased (attenuated) the pathology lesion in mice lung. A novel PEGylated CVN derivative, PEG20k –LCVN, exhibited potent and strain-dependent anti-IAV activity in nanomolar concentrations in vitro, as well as in micromolar concentration in vivo .